Analisis kesulitan belajar IPS tema 1 “indahnya kebersamaan” pada siswa kelas IV sskolah dasar - Candra Mustika Dewi; Jenny Indrastoeti Siti Poerwanti; Sularmi Sularmi (Universitas Sebelas Maret, 2022)
The results of this study indicate that the fourth grade students of SDN Bangunjiwo in participating in Social Studies learning Theme 1 The Beauty of Togetherness has learning difficulties. Students' learning difficulties occur in the affective, psychomotor, and cognitive domains. Students' learning difficulties are caused by two factors, namely internal and external. Based on the results of the study, it can be concluded that students have difficulty in Social Studies Theme 1 in the affective domain, namely students who are not honest, lack discipline, and do not have confidence. In the psychomotor domain, students do not have the skills to read, write, communicate, and process information. Meanwhile, in the cognitive domain, students' scores that were still below the KKM when working on test questions with material diversity in Indonesia were 19 students. students have difficulty learning Social Sciences Theme 1 due to interests, talents, motivation, schools, teachers, and parents.